The Authority of Bapemperda in the Formation of Regional Regulations: The Perspective of State Administrative Law in the City of Mataram - Primasari, Shinta; Hasanah, Siti; Jiwantara, Firzhal Arzhi (IHSA Institute, 2025)
The purpose of this study is to find out how To find out how the authority of the Regional Regulation Formation Agency of the Mataram City DPRD in the preparation of Regional Regulations in Mataram City. And To find out how the implementation of the authority of the Regional Regulation Formation Agency of the Mataram City DPRD. This type of research is normative-empirical. By using the Conceptual approach method (Conceptual Approach), Statute Approach (Statute approach) and Historical Approach (Historical Approach). Methods and techniques for collecting data through interviews, observations and documentation, using qualitative descriptive data analysis. The results of the study show that; The Legislative Function of the Mataram City Regional People's Representative Council is one of the attribution authorities inherent in the formation of regional regulations which begins at the planning, drafting, discussion and enactment stages. In carrying out its function as Legislation, it certainly requires complete tools in the DPRD structure itself, especially in the formation of Regional Regulations which in this case are carried out by Bapemperda which has the authority to harmonize, round off, and strengthen the concept of draft Regional Regulations submitted by members, commissions, or joint commissions before the draft Regional Regulation is submitted to the Leadership of the Regional People's Representative Council, Following the discussion of draft Regional Regulations submitted by the Regional People's Representative Council and the Regional Government, Providing considerations on proposals for the preparation of draft Regional Regulations submitted by the Regional People's Representative Council and the Regional Government outside the Regional Regulation formation program, Providing considerations to the Leadership of the Regional People's Representative Council regarding draft Regional Regulations originating from the Regional Government, Following developments and conducting evaluations on the discussion of the material contents of the draft Regional Regulation through coordination with the commission and/or special committee, Providing input to the Leadership of the Regional People's Representative Council on draft Regional Regulations assigned by the deliberative body, Conducting a study of Regional Regulations, Making a performance report at the end of the membership period of the Regional People's Representative Council and inventorying problems in the formation of both, the Regional Regulation Formation Agency of the Mataram City Regional People's Representative Council in implementing the authority to form The Regional Regulation has been running properly. This can be seen from how the Regional Regulation Formation Agency of the Mataram City Regional People's Representative Council has fulfilled the procedures or all applicable provisions in the process of forming regional regulations.